Perbandingan Hipersensitivitas Tipe IV Akibat Paparan Remanium Gm800 Dan Stainless Steel 316L - Ikmal Hafizi; Widjijono Widjijono; Marsetyawan HNE Soesatyo (Ikatan Peminat Ilmu Material dan Alat Kedokteran Gigi (IPAMAGI), 2017)
Stainless steel and cobalt chromium is a metal that is used in dentistry. Stainless steel (SS) 316L has good corrosion resistance, but there are still many cases of hypersensitivity due to the use of such materials. Remanium GM800 is a cobalt-based alloy which is relatively mild with the advantages of having a high fracture resistance, high modulus of elasticity and resistance to corrosion. The research aims to know type IV hypersensitivity reactions for cobalt chromium GM800 applications compared with 316L Stainless steel. The research was conducted through the test GPMT (Guinea Pig Maximization Test). The pre-research phase does CoCr patch/SS/control application to 3 guinea pigs of each group with concentrations of 5%, 10%, 20%, 40%, and 80%. Primary research begins with intradermal induction on the backs of guinea pigs for 7 days with a suspension of A (50% FCA emulsion dan 50% Propylene glycol), B (SS/CoCr/blank dan Propylene glycol) and C (50% SS/CoCr/blank suspension and 50% FCA) on the left and right backs of guinea pigs. On the 8th day induction results topical concentration of 40% for 24 hours, then opened to see the reaction and closed again for 48 hours. After that, the research was continued with challenge phase by attaching patch 5% concentration for 14 days. On the 28th day was observed erythema and edema on the skin of guinea pigs followed by sacrifice in order to obtain specimen to do immunohistochemical staining by ED antibodies. The result showed 316L SS cause 40% of the samples sensitized that were grouped in moderate classification, while CoCr GM800 cause 20% of the samples sensitized so classified in the mild classification in triggering type IV hypersensitivity reaction. Histopathology examination showed that 42% of the visual field SS 316L specimen expressed macrophages, while only 28% expressed macrophages in CoCr GM800 specimen. The conclusion of this study CoCr GM800 trigger type IV hypersensitivity reaction is lower than SS 316L.